NATIONAL IDENTITY NARRATIVES IN PRESIDENTIAL ADDRESSES TO THE UNITED NATIONS GENERAL DEBATE - Juraeva Guljakhon (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article examines the construction and communication of national identity narratives in presidential addresses delivered at the United Nations General Debate. Presidential speeches at the United Nations serve not only as diplomatic statements but also as instruments for presenting national values, historical experiences, political priorities, and visions of the international order. Through discourse analysis, the study explores how political leaders employ language, symbolism, and rhetorical strategies to strengthen national identity while engaging with global audiences. The findings suggest that national identity narratives play a crucial role in shaping international perceptions, legitimizing foreign policy decisions, and reinforcing domestic political legitimacy. The article highlights the significance of presidential discourse in contemporary international relations and diplomatic communication.
Keywords: Keywords: national identity, presidential discourse, United Nations, General Debate, political communication, diplomacy, rhetoric, international relations.